2000
DOI: 10.1007/s11745-000-0657-0
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a fluorescent bezafibrate derivative (DNS‐X). A new tool to study peroxisome proliferation and fatty acid β‐oxidation

Abstract: The first peroxisome proliferator-activated receptor (PPAR) was cloned in 1990 by Issemann and Green. Many studies have reported the importance of this receptor in the control of gene expression of enzymes involved in lipid metabolic pathways including mitochondrial and peroxisomal fatty acid beta-oxidation, lipoprotein structure [apolipoprotein (apo) A2, apo CIII], and fatty acid synthase. By using radiolabeled molecules, it was shown that peroxisome proliferators bind and activate PPAR. As an alternative met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It is also known that BEZA triggers the β-oxidation of fatty acids [34] and that acetate is needed for AF synthesis [5], [35] and, in relation to this, the enhancement of β-oxidation can fulfil this necessity; nevertheless, several papers have clearly shown that oxidative stress is a prerequisite for AF synthesis [12][14]. Being peroxisomes also a site for ROS and oxylipins generation [4], [36], [37], we sought the existence of a correlation among peroxisomal proliferation, the alteration of the cell redox balance, the formation of oxylipins and the biosynthesis of AF in A. flavus .…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that BEZA triggers the β-oxidation of fatty acids [34] and that acetate is needed for AF synthesis [5], [35] and, in relation to this, the enhancement of β-oxidation can fulfil this necessity; nevertheless, several papers have clearly shown that oxidative stress is a prerequisite for AF synthesis [12][14]. Being peroxisomes also a site for ROS and oxylipins generation [4], [36], [37], we sought the existence of a correlation among peroxisomal proliferation, the alteration of the cell redox balance, the formation of oxylipins and the biosynthesis of AF in A. flavus .…”
Section: Discussionmentioning
confidence: 99%
“…T o elucidate the interactions between ligands and PPARs or other peroxisome binding proteins, we developed a new probe, a fluorescent bezafibrate derivative, DNS-X [ 141. This molecule is able to trigger peroxisome proliferation both in oitro [14] and in oioo [15] and to undergo a PPARa activation by transfection assays. The PPAR-DNA response element is a direct repeat motif with a consensus sequence of TGACCT(T/A)TGACCT [16].…”
Section: Lipid Tmentioning
confidence: 99%